THE BALANCE OF SECULAR AND RELIGIOUS PRINCIPLES IN THE EARLY ARAB CALIPHATE - Zakhidov K., (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Abstract: This article explores the balance between secular and religious principles in the formation and governance of the early Arab Caliphate. It examines the political, administrative, and philosophical foundations of early Islamic rule, showing how Caliphs combined spiritual authority with practical governance. The study further discusses the concepts of ijtihad (independent reasoning) and maslaha (public welfare) as mechanisms of dynamic adaptation within Islamic political philosophy. The article also delves into the practical application of shura (consultation), economic policies, and the early development of judicial autonomy to provide a more comprehensive picture. Ultimately, it argues that the early Caliphate represented a unique synthesis between divine law and rational state management, forming the intellectual basis for later Islamic political and legal thought.